How to Manage Migration Flows through a New Model of Development: Inter-ethnic Companies as Good of Order in DRC - Ciminello, Romeo (European Journal of Sustainable Development, 2018)
Development of global companies must face the risks of diversity and intercultural dialogue, relating to space, time, habits, rites and customs, beliefs and substantiality of the memory of social events. The relational risks are the distinctive "character" of a people: Risks of language, religious, diversity of "values", of "different customs", of perceived education and of various contrasts. Migration flows must be managed in the context of an "Ethical Neo-capitalism". Key points of the project idea: to create development opportunities in the countries of origin with a replicable development model with a multiplier of 1 to 5; to create Cooperatives or Inter-ethnic companies (made up of people of different ethnicities, Europeans and Africans in the diaspora) in the various sectors: credit/agriculture/trade/services/mutuality and infrastructures, proportionally weighted among competent bodies chosen in Italy and in the DRC. The training is divided into two precise moments: a theoretical period in Italy and a period of practical "incubation" in DRC; In Italy: specific courses lasting three to six months and also for trainers, with people already belonging to the sector; the three-month African incubators; Courses in Italy could be financed both by the Italian Development Cooperation and by other possible interested Bodies. Identify in Africa, where and with whom and how, create incubators. During the year of preparation, inter-ethnic companies will have to be able to access a concession (with a privileged system) on which to start the business. Each company will take root in the city with at least 5 thousand inhabitants. The development model will have to be elaborated by points, by sector, by activity, organization, professionals, times and methods to be replicated in the different provinces or territories, where there are large human aggregates. Keywords: Development, Relational risks, Migrations, Ethical -, Neocapitalism, Cooperation